Pengembangan Media PAPIN (Papan Pintar) Kegimi (Kegiatan Ekonomi) Pada Mata Pelajaran IPS Kelas 4 SD Negeri 142 Palembang - Anissa syalsadilla; Kiki Aryaningrum M.Pd; Hetilaniar, M.Pd (CV. ITTC INDONESIA, 2024)
Based on the problems at SD Negeri 142 Palembang, the lack of use of media in social studies learning makes it difficult for students to understand the material on theme 8